The law of collaborative defence procurement in the European Union / Baudouin Heuninckx. - Heuninckx, Baudouin (Cambridge University Press, 2017)
States increasingly cooperate to buy expensive defence equipment, but the management and legal aspects of these large collaborative procurement programmes are complex and not well understood. The Law of Collaborative Defence Procurement in the European Union analyses how these programmes are managed, and highlights areas which require improvement. The book addresses the law applicable to these programmes, which is built upon a four-layer 'matryoshka doll' of legal relationships at the crossroads of public international law, EU law and domestic law. Using practical examples, the book makes proposals for clarifying the legal basis and improving the efficiency of defence equipment cooperation among EU member states. By covering a broad scope of legal issues, this analysis goes beyond the defence sector and is relevant to centralised or joint purchasing and procurement activities of international organisations, providing invaluable information for practitioners, policy-makers and academics aiming to analyse or improve these projects.